2011
DOI: 10.1007/s11182-011-9654-8
|View full text |Cite
|
Sign up to set email alerts
|

Multicyclic fatigue of stainless steel treated by a high-intensity electron beam: surface layer structure

Abstract: It is shown that an electron-beam treatment of the 08Х18Н10Т steel specimens under the condition of melting of the ~5 µm surface layer (electron beam energy density 25 J/cm 2 ) increases their fatigue life by a factor of 3.5. The structural-phase states and defect substructure of this steel are studied by the methods of optical, scanning and transmission electron microscopy, and the factors responsible for its increased fatigue life are revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…Forms and sizes of samples used in fatigue testing were similar to those in studies [ 26 , 28 ] and are shown in Figure 1 . To be precise, they were prepared as a parallelepiped with dimensions of 8 × 14 × 145 mm.…”
Section: Methodsmentioning
confidence: 66%
“…Forms and sizes of samples used in fatigue testing were similar to those in studies [ 26 , 28 ] and are shown in Figure 1 . To be precise, they were prepared as a parallelepiped with dimensions of 8 × 14 × 145 mm.…”
Section: Methodsmentioning
confidence: 66%
“…Various methods to form gradient structures have been discussed in some publications. For example, the surface modification (for instance, by concentrated flows of charged particles) has been widely applied to increase fatigue life [ 12 , 13 , 14 ]. However, according to the authors, the approaches based on the initiation of shear strains under the highly constraint conditions are of the greatest interest.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have paid attention to differences in fatigue resulting from the load [3][4][5][6][7][8][9][10][11][12]. A different fatigue life may correspond, as a result, to the same strain or stress curve.…”
Section: Introductionmentioning
confidence: 99%